2012
DOI: 10.1039/c2jm32160b
|View full text |Cite
|
Sign up to set email alerts
|

Vapochromic and mechanochromic films from square-planar platinum complexes in polymethacrylates

Abstract: Square-planar platinum(II) complexes of the 4-dodecyloxy-2,6-bis(N-methylbenzimidazol-2 0 -yl) pyridine ligand have been blended into a series of methacrylate polymers. Each of the polymer films displayed vapochromic (yellow to red) and vapoluminescent behaviour as a result of the vapour induced change in the Pt-Pt interactions. The solid-state absorption and emission properties of the films were characterized, and the influence of the polymer matrix on the vapochromic response was investigated. Notably, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 83 publications
(103 reference statements)
0
45
0
Order By: Relevance
“…Towards that end, the integration of Pt II chromophores into organic/inorganic functional materials might be one of the most promising approaches to create intelligent sensory systems. In this context, recently reported vapochromic films composed of organic polymers combined with Pt II molecular chromophores are promising candidates for practical application 83. Immobilization of the molecular Pt II chromophore in the cavity of microporous materials is also an interesting approach because the porous materials can provide selective gas/vapor adsorption, thereby resulting not only in improvement of the vapochromic response at low vapor concentrations, but also in quantitative detection of VOC vapors.…”
Section: Resultsmentioning
confidence: 99%
“…Towards that end, the integration of Pt II chromophores into organic/inorganic functional materials might be one of the most promising approaches to create intelligent sensory systems. In this context, recently reported vapochromic films composed of organic polymers combined with Pt II molecular chromophores are promising candidates for practical application 83. Immobilization of the molecular Pt II chromophore in the cavity of microporous materials is also an interesting approach because the porous materials can provide selective gas/vapor adsorption, thereby resulting not only in improvement of the vapochromic response at low vapor concentrations, but also in quantitative detection of VOC vapors.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the possibility of changing the glass transition of the polymer matrix (T g ) with the length of the methacrylate chain allowed to investigate the role of T g in the response of the luminescent Pt complexes embedded in polymers. 75 It was found that mechanical as well as vapochromic response of complex 16 (Chart 2) was detectable and stable for high T g polymers (poly(methyl methacrylate), T g = 90°C), while the same response was only temporary when T g approached room temperature (poly(butyl methacrylate), T g = 30°C), as shown in Figure 14. Furthermore, as soon as each polymer mixture was heated above its T g , the luminescence could be reset to the initial®non ground®state, while attempts to stress the films above T g gave no observable response, due to the tendency of the polymer to flow, and thus to absorb the mechanical energy conveyed for structural rearrangement of the Pt(II) complex crystals.…”
Section: Mechanochromic Systemsmentioning
confidence: 89%
“…[16][17][18] The success of such dye/polymer systems is largely due to the ability of VOCs to spread rapidly inside the polymer matrix and to interact with the dye providing the means for a fast and reliable response. [19][20][21] Moreover, most of the polymers are colourless with good lm forming features, which allows the preparation of large area devices under ambient conditions and by means of low cost fabrication techniques.…”
Section: Introductionmentioning
confidence: 99%